PENTINGNYA PENDIDIKAN AGAMA ISLAM TERHADAP AKHLAK PESERTA DIDIK - Wulandari, Dewi (Jurnal Ilmiah Pendidikan dan Keislaman, 2022)
Islamic religious education is a conscious effort made by educators in order to prepare students to believe, understand, and practice Islamic teachings through guidance, teaching or training activities that have been determined to achieve the goals that have been set. The importance of Islamic religious education on the morals of students because by carrying out moral education, the development of students will develop aqidah through giving, fertilizing, developing, knowledge, habituation, and the experience of students about the religion of Islam and students can become a devout Muslim and have good character. noble and firm in faith and devotion to Allah SWT in accordance with Islamic law. Morals that must be possessed by students are: 1. Praiseworthy morals or morals, namely the moral group that should be owned by a Muslim. Maheasy character includes patient, honest, humble, generous, polite, persistent, willing to sacrifice, fair, wise, gentle and polite and trust in Allah SWT. 2 Morals towards Allah SWT, where humans are given perfection and advantages compared to other creatures. Humans are also given reason to think, feel and lust. So that we should have good morals towards Allah SWT, 3. Morals as parents, of course children become a mandate entrusted by Allah SWT to their parents. Our obligations as parents are to give a good name, slaughter the aqiqah animal on the seventh day of its birth, circumcise it, give love, provide a living, provide education, especially those related to religion and marry it to a good partner after adulthood, 4. Morals towards fellow human beings Islam teaches that humans should always maintain and develop good relations between fellow human beings including with neighbors and this obligation is considered important because it can affect the quality of one's faith.